2018
DOI: 10.1016/j.jmaa.2018.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Spectral properties of tensor products of channels

Abstract: We investigate spectral properties of the tensor products of two completely positive and trace preserving linear maps (also known as quantum channels) acting on matrix algebras. This leads to an important question of when an arbitrary subalgebra can split into the tensor product of two subalgebras. We show that for two unital quantum channels the multiplicative domain of their tensor product splits into the tensor product of the individual multiplicative domains. Consequently, we fully describe the fixed point… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…A uniform upper bound for the multiplicative index may provide an upper bound for this number. In a recent article [8], Theorem 3.8, such a bound for multiplicative index of a channel was proposed. Also analyzing the structure of PPT maps in Section 3, it can be realized that to prove the PPT-squared Conjecture (1.1) it is enough to prove the same for unital and trace preserving PPT maps which have trivial multiplicative domain.…”
Section: Discussionmentioning
confidence: 99%
“…A uniform upper bound for the multiplicative index may provide an upper bound for this number. In a recent article [8], Theorem 3.8, such a bound for multiplicative index of a channel was proposed. Also analyzing the structure of PPT maps in Section 3, it can be realized that to prove the PPT-squared Conjecture (1.1) it is enough to prove the same for unital and trace preserving PPT maps which have trivial multiplicative domain.…”
Section: Discussionmentioning
confidence: 99%
“…Grayscale (think of the image as a 3D image of XY) 2. The gamma correction method is used to standardize the color space of the input image in order to adjust the contrast of the image, reduce the influence caused by the local shadow and illumination change of the image [26], and at the same time, suppress the noise interference 3. Calculate the gradient (including size and direction) of each pixel in the image, primarily to capture contour information while further attenuating the interference of light 4.…”
Section: Implementation Of Hog Feature Extraction Algorithmmentioning
confidence: 99%
“…A recent work [8] indicated that if we consider unital quantum memory cell E (E(I) = I) and use the decoherence-free subsystems storing quantum information, then the superactivation of quantum information cannot exist. So checking the existence for general quantum memory cells is also an interesting problem.…”
Section: Discussionmentioning
confidence: 99%